Dynamic Parameter Identification Based on Lagrangian Formulation and Servomotor-Type Actuators for Industrial Robots - Urrea-Onate, E; Pascal-Mamani, J (Institute of Control, Robotics and Systems, 2021)
This article presents the design of a parameter identification model for industrial manipulator robots. This model includes the dynamics of servomotor-type actuators and therefore is formulated based on acceleration, speed, position and voltage applied to the actuator. In this way, calculating the torque of a joint during motion to estimate parameters, as in the Inverse Dynamic Identification Model (IDIM), is unnecessary. The model proposed is satisfactorily applied to the parameter identification of an industrial redundant robot with 5 Degrees of Freedom (DoF). © 2021, ICROS, KIEE and Springer.